2020
DOI: 10.1101/2020.02.25.20027755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application and optimization of RT-PCR in diagnosis of SARS-CoV-2 infection

Abstract: syndrome coronavirus 2 (SARS-CoV-2) has become a global threat to public health. Aiming to construct an efficient screening pattern, we comprehensively evaluated the performances of RT-PCR and chest CT in diagnosing COVID-19. Methods:The records including demographics, RT-PCR, and CT from 87 confirmed cases and 481 exclusion cases were collected. The diagnostic accuracy of the pharyngeal swab RT-PCR, CT, combination with the second pharyngeal swab RT-PCR or with CT were evaluated individually.Besides, all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 24 publications
2
41
0
2
Order By: Relevance
“…assay is widely used in the early diagnosis and monitoring of SARS-CoV-2 infections. RT-PCR was positive in 59 to 78.2% of cases [5,6,61]. This assay may detect the viral RNA in the early stage of clinical symptoms even with negative CT findings [62].…”
Section: Laboratory Findings A) Diagnostic Tests-reverse Transcriptiomentioning
confidence: 84%
See 2 more Smart Citations
“…assay is widely used in the early diagnosis and monitoring of SARS-CoV-2 infections. RT-PCR was positive in 59 to 78.2% of cases [5,6,61]. This assay may detect the viral RNA in the early stage of clinical symptoms even with negative CT findings [62].…”
Section: Laboratory Findings A) Diagnostic Tests-reverse Transcriptiomentioning
confidence: 84%
“…Fever and cough are the most common clinical symptoms. Abnormal chest computed tomography (CT) has been used to diagnose 67.4-88.0% cases of COVID-19, indicating that pneumonia is the most common manifestation of the disease [4][5][6]. Therefore, CT imaging is widely used in the early diagnosis of the disease, but chest CT may not distinguish COVID-19 from other viral pneumonias [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that some patients with a negative COVID-RT-PCR test displayed abnormalities on lung CT-scan [14], questioning the sensitivity of the RT-PCR test. It appears that the combination of RT-PCR and lung CT-scan lead to the highest diagnostic sensitivity [15] (92%) compared to RT-PCR alone (78%), lung CTscan alone (67%) or combination of 2 RT-PCR (86%). Combination of both RT-PCR test and lung CT-scan to exclude COVID-19 patients is thus recommended to limit the risk to bring infected patient to surgery.…”
Section: Pre-operative Screeningmentioning
confidence: 99%
“…The use of quantitative real-time PCR (qRT-PCR) assays for the detection of the viral nucleic acid has become the primary and crucial diagnostic approach for identification of SARS-CoV-2 infection, while it still has some limitations in clinical practice (7)(8)(9). The RNA-based diagnostic tests only give a positive result when the virus is still present.…”
Section: Introductionmentioning
confidence: 99%